The Training Innovation Of Meatballs For Additional Seaweed Post Covid-19 Pandemic In Pankep Regency - Fatmawati Fatmawati; Aminuddin; Saiman Sutanto; Abdul Halik; Andi Liswahyuni; Aminah (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Pangkep Regency, Anrong Appaka Village, is a seaweed producing area, and is a leading commodity for fishery products. Seaweed cultivation is a farming business by the community. However, farmers do not have the knowledge and skills in postharvest processing, so it becomes a problem for farmers. This PKM aims to provide training and counseling to the community as a solution to the model of Selling Picks Cultivation into Selling Picks. The Pangkep Regency Government considers this activity very good for relaxing and restructuring the knowledge and skills of the community in general, especially farmer groups in the post-covid-19 pandemic atmosphere. Through this service activity, it is hoped that the problems experienced by seaweed farmers will get solutions from service lecturers through various methods, namely observation, surveys, Focus Group Discussions, with training and counseling techniques. The results of community service activities that can increase the knowledge and skills of the community, especially farmers in post-harvest management of seaweed, can even build an independent entrepreneurial spirit through innovative meatballs with the addition of seaweed